Study on Galvanic Corrosion Characteristics of Metallic Materials Used in Surface Ships - WU Xing - wei, HUANG Lu - qiong, SUN Qi (Cailiao Baohu)
Surface ships are made of many metallic materials, and galvanic corrosion is easy to occur when these materials in the same system are without insulation. In this work, the common metallic materials used in ships were selected to form 15 kinds of different metal galvanic couples for conducting galvanic corrosion tests, and the galvanic corrosion characteristics of metallic materials used in surface ships were obtained. Results showed that in the comparisons of other metals, TA2 and ZTA5 used as cathodes got the faster anodic corrosion rate and the more negative coupling potential was negative, and the galvanic corrosion rate increased as the area ratio increased. Moreover, copper alloy B10 and stainless steel 316L had little difference in galvanic corrosion. When 907 was connected with other metals, the coupling potential was more negative, which was very easy to occur galvanic corrosion, so attention should be paid to the protection of electrical insulation. Therefore, titanium alloys should be avoided directly coupling with other metals, and 907 used on surface ships must to be treated with electrical insulation when connected with other metals.